Medical egg freezing and cancer patients’ hopes: Fertility preservation at the intersection of life and death - Inhorn, Marcia C.; Birenbaum-Carmeli, Daphna; Patrizio, Pasquale (Social science & medicine (1982), 2017)
Egg freezing (i.e., oocyte cryopreservation) is a new reproductive technology that allows women's eggs to be frozen and stored for future use. Over the past five years, so-called “medical egg freezing” (MEF) has begun to play a major role as a form of fertility preservation for young women with cancer and other fertility-threatening medical conditions. Indeed, women who are candidates for MEF are often facing the “double jeopardy” of fertility loss and potential death. In this article, we examine the experiences of the first generation of women to use MEF in the United States and Israel, two countries where experimental use of MEF began early, and where MEF is now offered clinically in many in vitro fertilization (IVF) clinics. Through an ethnographic, interview-based study carried out between June 2014 and August 2016 with 45 women (33 American, 12 Israeli) who had completed at least one cycle of MEF, we highlight women's reflections on their egg freezing experiences, and their considerable hopes for future recovery and motherhood. However, MEF is a Janus-faced new “hope technology.” On the one hand, it holds out the promise of life in terms of recovery and future childbearing. As such, women's reflections on MEF reveal hope and gratitude for the technology's existence. However, as with IVF itself, future motherhood can never be guaranteed. This is especially true for women facing death from advanced or aggressive forms of cancers. Three ethnographic case studies of cancer patients, two from the US and one from Israel, highlight how MEF offers hope for life among women confronted with a deadly disease. •First ethnographic study of women who have undertaken medical egg freezing (MEF).•Reveals women's hopes for survival and future childbearing through MEF.•Points to the “double jeopardy” of fertility loss and death facing cancer patients.•Examines the experiences of women with advanced and aggressive cancers.•Provides ethnographic cases from two countries (United States and Israel).